Criminalization Of Adultery During The Covid 19 Pandemic - Siti Nurfadila Rahman (Estudiante Law Journal, 2020)
The purpose of this study is to find out the criminology of adultery perpetrators during the Covid 19 Pandemic. The type of research used is empirical legal research. While sample withdrawal uses purposive sampling and data analysis using qualitative research approaches. The results showed that cases of adultery occur of course triggered by various factors both internal factors and external factors. In the current pandemic period where the majority of people ranging from high economic class to low economic class experience severe economic crisis, primary and secondary needs are difficult to meet to cause feelings of stress and stress that can trigger quarrels in the household, these quarrels can also trigger divorce in households caused by the economy or other actions. In addition, the problem of economic crisis can also trigger adultery were to meet the economy, they commit such unworthy deeds to earn money as well as commercial sex workers. There needs to be increased understanding of the law by law enforcement and the government towards citizens to avoid actions that can harm themselves and others, especially legal counseling to the younger generation.